2016
DOI: 10.1186/s12944-016-0387-0
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate attenuates lipolysis in adipocytes co-cultured with macrophages through non-prostaglandin E2–mediated and prostaglandin E2–mediated pathways

Abstract: BackgroundInteractions between adipocytes and macrophages are associated with metabolic disorders. Production of pro-inflammatory mediators and the release of free fatty acids (FFAs) increase when these cells are co-cultured; butyrate significantly diminishes these effects by suppressing both the macrophage inflammatory and adipocyte lipolysis pathways. Butyrate is known to up-regulate the expression of prostaglandin E2 (PGE2). Therefore, we hypothesized that PGE2 is associated with the suppression of lipolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…In fact, FFA loading is a common in vitro model to evaluate the effects of various agents on lipid accumulation (steatosis) in hepatocytes. It had been reported that coculture with macrophages increases the release of FFA from adipocytes into the CM (34). FAA incubation has been found to significantly increase IL-6 expression, which can increase lipogenesis in cultured hepatocytes (4).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, FFA loading is a common in vitro model to evaluate the effects of various agents on lipid accumulation (steatosis) in hepatocytes. It had been reported that coculture with macrophages increases the release of FFA from adipocytes into the CM (34). FAA incubation has been found to significantly increase IL-6 expression, which can increase lipogenesis in cultured hepatocytes (4).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, oral administration of SCFAs (acetic acid, propionic acid, and butyric acid) decreases the concentration of triglyceride (TG) and could attenuate the fat deposition of pigs [76]. In addition, evidence in mouse and human also demonstrates that SCFAs modulate adipogenesis and attenuate lipolysis [77][78][79][80][81][82][83]. Therefore, SCFAs regulate energy metabolism via activating their receptors on adipocytes, which may produce adipokines such as leptin to participate in the development of CVDs.…”
Section: Scfas and Adipose Tissuementioning
confidence: 99%
“…A previous study suggested that NEFA concentrations in the circulation are more directly associated with liver injury than other parameters such as TAG deposition or TAG concentration in the circulation [60]. Other studies have also demonstrated a reduction in NEFA in mice treated with butyrate or Tb, associating this effect with inhibition of adipocyte lipolysis [39,61,62]. In our study, we found that, regardless of the genetics of mice (C57BL/6, Gpr43 −/− or Gpr109a −/− ), Tb decreased NEFA in serum, supporting the premise that this effect was not related to the activation of GPR43 or GPR109A, as we expected.…”
Section: Discussionmentioning
confidence: 99%